ANALISIS YURIDIS NOVASI PERJANJIAN PRODUK TOUR PADA BIRO JASA PERJALANAN DI MEDAN - Darwis Chandra Chandra (jurnal.unprimdn.ac.id, 2018)
The research that we do in order to find out the juridical review for the application of a service product by a travel business for consumers to measure responsibility in a new contract (Addendum) that happen Force Majuere in journey of Bangkok Pattaya that contain Novation and Addendum according of Act No. 8 of 1999 concerning consumer protection and the contract law in the civil law. This research that review the main problem of the consumer protection law which measured in yuridition normative – empirical approach. In the normative – empirical research method also about the implementation of the normative law that contain of the action on a certain event that happen in social environment that doing by description analition that a researching with description, study and analysis of a law.